Safe assets, risky assets, and dynamic inefficiency in overlapping-generations economies - Martin Hellwig (Max Planck Institute for Research on Collective Goods, 2021)
The paper gives conditions for dynamic inefficiency of laissez-faire allocations in an overlapping-generations model with safe and risky assets. If the rate of population growth is certain, the conditions given depend only on how the rate of return on safe assets compares to the growth rate. If no safe assets are held, the implicit relative price for non-contingent intertemporal exchanges takes the place of the safe rate of return. Returns on risky assets do not enter the comparison. The conclusion holds regardless of whether welfare assessments are made from an interim perspective, taking account of the information that people have, or from an ex ante perspective. If a laissez-faire allocation is dynamically inefficient, a Pareto improvement can be implemented by a suitable fiscal policy intervention, which includes specific taxes or subsidies that neutralize incentive effects on risky investments and the price effects they induce.
hdl:21.11116/0000-0008-6AAA-2
Keywords: D15; D61; E21; E22; E62; H30; 330; Dynamic Inefficiency; overlapping-generations models; safe asset shortages; macro risk allocation; public debt